(untitled) - Houck, Thomas P. (Hoboken, NJ, 2003)
When recent business scandals caused the credibility of independent audits to plummet, investors and the business community largely lost faith in the ability of auditors to adequately fulfill their professional responsibilities. Despite recent legislation designed to improve audit quality in the United States, the conditions that most often lead to ineffective audits have not been adequately addressed. Why and How Audits Must Change: Practical Guidance to Improve Your Audits describes the essential steps that accounting firms must take to improve audit quality. The author provides detailed coverage of important topics such as risk-based auditing techniques, analytical procedures, technology, and internal controls. After explaining why frequently used audit approaches are inadequate for detecting material fraud, the author: Provides specific and practical guidance to help auditors conduct higher quality audits. Offers guidance to financial executives on ways to evaluate their independent audits. Describes the steps that accounting firms must take to implement these much-needed changes. Utilizing a wealth of practical examples and case studies, the author shows today’s auditors and accounting firms how to significantly improve the overall quality of their audit engagements. He also makes a convincing case that auditing can be rewarding, exciting, and profitable. Since the techniques outlined are also applicable to government agencies and international organizations, the text will also be of significant value to auditors working in governmental and global arenas. And in today’s shaky economic climate, this book is an important resource for executives and senior management who want to take a more proactive role in ensuring the accuracy of their companies’ financial statements.
Keywords: Auditing,Auditing, analytical review